PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. SUMBER TRIJAYA LESTARI AREA KERJA TANGERANG SELATAN - Kurnia Eka Febriyanti; Melda Wiguna (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the influence of organizational culture and work discipline, both partially and simultaneously, on employee produktivity at PT. Sumber Trijaya Lestari. The research applied an associative method with a quantitative approach. Data were collected through questionnaires distributed to60 respondents and analyzed using validity and reliability tests. The results confirmed that all indicators were valid ( r count > r table 0,2542) and reliable, with Cronbach’s Alpha values of 0,931, 0928, and 0,945 for organizational culture, work discipline, and employee productivity, respectively.Simple regression analysis shows that organizational culture significantly affects employee produktivity with the regression model Y = 30,093 + 0,574X1, supported by t count 5,533 > t table 1,672 and a significance value of 0,000 < 0,05. The correlation coefficient 0f 0,588 idicates a moderately strong relationship, with a determination coefficient 0f 34,5%. Similarly, work discipline significantly influences employee produktivity with the regression model Y = 33,981 + 0,516X2, tcount 4,302 > t table 1,672, significance 0,000 < 0,05, a correlation coeficient of 0,492, and a determination coefficient of 24,2%.Furthemore, multiple regression analysis confirms the organizational culture and work discipline simultaneously have a significant effect on employee productivity, with F count 15,043 > F table 3,08 and significance 0,000 < 0,05. The determination coefficient 0f 34,5% demonstrates that employee productivity is jointly explained by these two variables.